Pengaruh Inovasi Program Kemanusiaan terhadap Budaya Organisasi dan Kinerja Karyawan pada Asia Muslim Charity Foundation - Muhammad Romli; Ahmad Faisal Siregar (Jurnal Ekonomi, 2021)
The purpose of this study was to determine the effect of humanitarian program innovation on organizational culture and employee performance at the Asia Muslim Charity Foundation. This study uses an explanatory survey method, namely the research method is carried out on large and small populations, but the data studied are data taken from samples from that population, so that descriptions and relationships between variables are found. In order for the sample in this study to be said to be representative, the method in this study uses the Slovin formula from the total population with a precision (error) level of 5% and obtained as many as 99 employees who are the object of research where all employees have the same opportunity to be used as samples of this study. . Data was collected through questionnaires as the main data collection, supported by interviews and literature study. The analysis technique used is path analysis. Based on the results of the study, it can be concluded that organizational culture has a significant effect on humanitarian program innovation, employee performance has no significant effect on humanitarian program innovation, and organizational culture does not have a significant influence on humanitarian program innovation through employee performance at the Asia Muslim Charity Foundation.